1993
DOI: 10.1037/0278-7393.19.6.1235
|View full text |Cite
|
Sign up to set email alerts
|

Illusions of familiarity.

Abstract: Feelings of familiarity are not direct products of memory. Although prior experience of a stimulus can produce a feeling of familiarity, that feeling can also be aroused in the absence of prior experience if perceptual processing of the stimulus is fluent (e.g., Whittlesea, Jacoby, & Girard, 1990). This suggests that feelings of familiarity arise through an unconscious inference about the source of processing fluency. The present experiments extend that conclusion. First, they show that a wide variety of feeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
744
2
20

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 633 publications
(802 citation statements)
references
References 33 publications
36
744
2
20
Order By: Relevance
“…In that case, it is the speed and ease of processing resulting from both repeated exposure (see Jacoby & Dallas, 1981) and high-quality stimuli (e.g., Checkosky & Whitlock, 1973;Whittlesea et al, 1990) that influence peopleÕs decision processes: the absolute magnitude of fluency resulting from the various sources can have a direct impact on peopleÕs preference and recognition decisions. These findings tally, on the one hand, with the fluency account of the mere exposure effect (Bornstein & DÕAgostino, 1994;Seamon et al, 1983aSeamon et al, , 1983bWhittlesea, 1993;Whittlesea & Price, 2001), and on the other hand, with the well-established idea that fluency may serve as a cue for various judgments (such as recognition, through the familiarity feeling, e.g., Jacoby & Dallas, 1981;Whittlesea et al, 1990). In Experiment 2, with a more perceptible but still unnoticed quality difference at the time of testing, the pre-exposure influence was particularly great when target stimuli were presented with a low-quality level.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…In that case, it is the speed and ease of processing resulting from both repeated exposure (see Jacoby & Dallas, 1981) and high-quality stimuli (e.g., Checkosky & Whitlock, 1973;Whittlesea et al, 1990) that influence peopleÕs decision processes: the absolute magnitude of fluency resulting from the various sources can have a direct impact on peopleÕs preference and recognition decisions. These findings tally, on the one hand, with the fluency account of the mere exposure effect (Bornstein & DÕAgostino, 1994;Seamon et al, 1983aSeamon et al, , 1983bWhittlesea, 1993;Whittlesea & Price, 2001), and on the other hand, with the well-established idea that fluency may serve as a cue for various judgments (such as recognition, through the familiarity feeling, e.g., Jacoby & Dallas, 1981;Whittlesea et al, 1990). In Experiment 2, with a more perceptible but still unnoticed quality difference at the time of testing, the pre-exposure influence was particularly great when target stimuli were presented with a low-quality level.…”
Section: Resultsmentioning
confidence: 56%
“…Several researchers suggested that enhanced processing fluency due to a previous encounter may serve as a basis for preference and produce the mere exposure effect (e.g., Bornstein & DÕAgostino, 1994;Jacoby, Kelley, & Dywan, 1989;Seamon, Brody, & Kauff, 1983a, Seamon, Brody, & Kauff, 1983bWhittlesea, 1993;Whittlesea & Price, 2001). Enhanced processing fluency can be defined as the ease with which information can be processed (as reflected by the speed and ease with which a stimulus is perceived), either at a perceptual level (i.e., subsequent to a perceptual encoding process involving that stimulus: perceptual fluency) or at a conceptual level (i.e., subsequent to a conceptual process involving information related to that stimulus: conceptual fluency).…”
Section: Introductionmentioning
confidence: 99%
“…perceptual fluency). Compared with a new item in a recognition test, an old item is more readily processed, which makes it more likely to feel familiar and provides the basis for an "old" response [71]. Recollection, on the other hand, is described as a consciously controlled retrieval of source-specific information from episodic memory.…”
Section: Introductionmentioning
confidence: 99%
“…We call this memory assessment and propose that it should be available by default even if very little of substance can be remembered. People using this type of strategy estimate frequency on the basis of how familiar the event seems (Whittlesea, 1993), how similar it is to encoded instances (Hintzman, 1988), or how available (easily brought to mind) relevant instances are (e.g., Tversky & Kahneman, 1973).…”
Section: The Multiple Strategy Perspective On Frequency Estimationmentioning
confidence: 99%